"I’s Natural Homicidal": Violence and Silence in Execution Poems - Mercer-James, Eshe (Pivot: A Journal of Interdisciplinary Studies and Thought, 2014)
The inescapable presence of violence throughout George Elliott Clarke’s oeuvre proposes that the silence imposed on the black community is only overcome through violence. The inevitability of violence is particularly evident in his collection Execution Poems. This collection recounts the “Tragedy of George and Rue,” cousins of his mother who killed and robbed a white taxi driver and were then the last people hanged as state punishment in New Brunswick. Through protagonists’ rationalizations for the crime and with their familial connection to him, Clarke collapses time and justice to place the black man outside of history and within violence. Silence then becomes a visceral experience for black males. Clarke suggests that Western society enacts its silencing of the black male through violence, thus combating this enforced voicelessness becomes a matter of violent vengeance: the only expression impossible to ignore. In a reflection of a peculiar position of blackness in Canada, the inescapability of violence for the black man who wishes to express his subjective being is grounded in a Western history of violence as retribution, which culminates in the diasporic struggle for black equality as enacted by black Americans. Clarke uses intertextual references to Shakespeare’s Titus Andronicus and the iconic slave rebellion leader Nat Turner to locate his characters in a greater mythology of the battle for self-actualization, for a voice. Clarke himself is implicated in this violence, despite his recuperative ability to write poetry. The violence which drives the aptly titled Execution Poems reflects his belief that black literature still functions as a transgression for the wider community. Clarke posits the escape from this silence as an inherent act of violence.